إستخدام معايير الحكم الشخصي في اختيار المشايع الاستثمارية في ظل ظروف عدم التأكد التام - بن معتوق, صابر; سراي, صالح (Université de M'sila, 2019)
تهدف هذه الداراسة إلى إبراز دور معايير الحكم الشخصي في اختيار المشاريع الاستثمارية وترشيد القرار الاستثماري في ظل ظروف عدم التأكد التام، نظراً لما تشهده بيئة اتخاذ القرار من تحولات وتغيرات مستمرة ومتسارعة، وقد اعتمدنا على المنهج الوصفي التحليلي لوصف وتحليل متغرات الدراسة، وقد توصلت هذه الدراسة إلى أنه ليس من المنتظر أن يتم اختيار نفس البديل الاستثماري في ظروف اللايقين التام، لأن سلوكيات متخذي القرار عادةً ما تكون مختلفة ومتباينة ومُتعارضة، وبالتالي يصعب التوصل إلى تحديد المعيار الذي يجب استخدامه بطريقة كافية وفعالة ومُرضية، إلا أن معيار سافاج (Savage) يُعتبر الأكثر تطبيقاً في اختيار المشاريع في ظل المستقبل المجهول. This study aims to highlight the role of the standards of personal governance in the selection of investment projects and rationalization of investment decision under conditions of uncertainty, given the environment in the decision-making of the shifts and changes are continuous and accelerated, We relied on descriptive analytical methodology to describe and analyze study variables, The study found that it is not expected that the same investment alternative will be chosen under conditions of complete uncertainty, because the behavior of decision makers is usually different, different and contradictory, It is therefore difficult to determine which criterion should be used in a sufficient, effective and satisfactory manner, but the Savage criterion is the most applicable in the selection of projects in the uncertain future.
Keywords: المشروع الاستثماري؛ القرار الاستثماري؛ ظروف عدم التأكد التام؛ المعاير الشخصية (الذاتية). .Investment Project ; Investment decision ; Uncertainty ; Personal criteria